2013
DOI: 10.3109/02770903.2012.761231
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Generation of Suppressor T Cells in Patients with Asthma Taking Oral Contraceptives

Abstract: INTRODUCTION A dysregulation of regulatory T cells (Tregs) could play a major role in the pathogenesis of bronchial asthma. Sex-dependent differences as well as the impact of hormonal changes in the incidence and severity of asthma are widely recognized. Emerging evidence suggests that asthma symptoms are alleviated in female patients taking hormone oral contraceptives (OCs). The impact of OCs on the generation of induced Tregs (iTregs) was assessed in a cohort of female patients with asthma. METHODS Thirtee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
1
15
0
2
Order By: Relevance
“…An exaggerated Th2-driven response is believed to lead the inflammatory allergic reaction of asthma. Particularly, Th2 cytokines induce the production of IgE and mast cells, activation and recruitment of eosinophils, and airway hyperreactivity and mucus secretion [ 59 ]. Of major importance are induced regulatory T cells (iTregs), which can inhibit or suppress the effector function of T helper cells and their tolerance to environmental allergens [ 59 61 ] thus preventing the induction or reducing the severity of asthma [ 59 61 ].…”
Section: Reviewmentioning
confidence: 99%
“…An exaggerated Th2-driven response is believed to lead the inflammatory allergic reaction of asthma. Particularly, Th2 cytokines induce the production of IgE and mast cells, activation and recruitment of eosinophils, and airway hyperreactivity and mucus secretion [ 59 ]. Of major importance are induced regulatory T cells (iTregs), which can inhibit or suppress the effector function of T helper cells and their tolerance to environmental allergens [ 59 61 ] thus preventing the induction or reducing the severity of asthma [ 59 61 ].…”
Section: Reviewmentioning
confidence: 99%
“…The findings in the literature are divergent, given that some studies have reported that estrogen and progesterone improve total lung capacity and reduce the exacerbation of asthma symptoms, such as coughing, wheezing and dyspnea. [37][38][39][40] In a study by Carlson et al, use of oral contraceptives (combined contraceptives) and unopposed forms of estrogens reduced hormone fluctuations and decreased premenstrual asthma. 41 In a study by Lange, no relationship was found between use of oral contraceptives and asthma.…”
Section: Use Of Hormone Contraceptives and Asthmamentioning
confidence: 99%
“…In this study, patients taking oral contraceptives showed reduced serum sex hormone levels, and this was associated with higher rates of iTreg induction, better asthma control test scores and a tendency towards lower exhaled nitric oxide (eNO) levels. 37 On the other hand, Guthikonda et al 47 reported that oral contraceptives and early menarche (via exogenous or endogenous hormones) were associated with the DNA methylation level of the Th2 transcription factor gene and GATA-3 and that they increased the risk of asthma among girls, possibly through interaction with genetic variants. This factor may explain how endogenous and exogenous hormones can, in women, increase the prevalence of asthma after puberty.…”
mentioning
confidence: 99%
“…Mouse models of asthma, allergy, and respiratory infections collectively confirm that (i) females suffer a worse outcome from pulmonary diseases than males, (ii) lung function changes with circulating 17␤-estradiol (E2) concentrations, and (iii) exogenous E2 treatment reduces pulmonary inflammation and symptoms of disease in females (9)(10)(11)(12)(13)(14)(15). In humans, administration of oral contraceptives that contain E2 reduces asthma exacerbations associated with premenstrual asthma by increasing regulatory T cell activity and reducing allergic inflammation in the respiratory tract (16). Sustained, as opposed to cyclical, concentrations of E2 are associated with improved outcome of respiratory diseases, including those caused by infections (11).…”
mentioning
confidence: 99%